The Effect Of Transformational Leadership And Motivation On Organizational Citizenship Behavior in Primary Schools - Rifqy Rahmansyah (STAI Hubbulwathan Duri, 2022)
Along with so many crucial roles for teachers in schools and the low competence of teachers in general, school institutions certainly need a catalyst to increase their effectiveness to produce an excellent education system. Teachers who are creative, adaptive, and full of initiative are no longer just a necessity but an urgency for every school. Organizational citizenship behavior (OCB) which is a positive voluntary behavior that exceeds the formal job requirements is expected to have positive implications for teacher performance. Existing studies found OCB has greatly benefited organizational outcomes. The aim of this study was to determine the effect of transformational leadership and motivation on organizational citizenship behavior in primary schools Kecamatan Pinang, Kota Tangerang, Indonesia. The sample in this research were 112 teachers in Pinang primary schools. The study used a quantitative approach with a survey method. Path analysis was utilized to determine between variables. These results indicate that transformational leadership has a direct positive effect on organizational citizenship behavior, motivation has a direct positive effect on organizational citizenship behavior, and transformational leadership has a direct positive effect on motivation. Thus, to improve organizational citizenship behavior in schools, school principals should practice transformational leadership and teachers should maintain the level of motivation. Banyaknya peran guru di sekolah dan masih rendahnya kompetensi guru secara umum, membuat institusi pendidikan jelas membutuhkan katalis dalam meningkatkan efektivitasnya agar bisa menciptakan sistem pendidikan yang unggul. Guru yang kreatif, adaptif, dan penuh inisiatif bukan lagi sekedar kebutuhan namun sudah menjadi urgensi bagi setiap sekolah. Organizational citizenship behavior (OCB) yang merupakan perilaku sukarela melampaui persyaratan pekerjaan formal diharapkan dapat memberikan implikasi positif terhadap performa guru. Kajian yang sudah ada menunjukkan bahwa OCB memberikan manfaat yang besar terhadap organisasi. Tujuan dari penelitian ini adalah mengetahui pengaruh kepemimpinan transformasional dan motivasi terhadap organizational citizenship behavior di Sekolah Dasar Negeri Kecamatan Pinang, Kota Tangerang, Indonesia. Sampel pada penelitian ini berjumlah 112 guru dari 10 sekolah di Kecamatan Pinang. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survey. Penelitian ini menggunakan analisis jalur. Hasil penelitian ini adalah, terdapat pengaruh positif kepemimpinan transformasional terhadap organizational citizenship behavior, terdapat pengaruh positif motivasi terhadap organizational citizenship behavior, dan terdapat pengaruh positif kepemimpinan transformasional terhadap motivasi. Kepala sekolah dapat menggunakan kepemimpinan transformasional dalam kepemimpinan manajemen dan guru dapat menjaga tingkat motivasi dalam rangka peningkatan organizational citizenship behavior di sekolah..